Penerapan Sistem Manajemen Keselamatan Pertambangan di Tambang Andesit PT. Gunung Kulalet Desa Baleendah, Kecamatan Baleendah, Kabupaten Bandung - Dedi Saputra; Yunus Ashari (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Implementation of Mining Safety Management System (SMKP) in this study has a legal basis for carrying out the instructions of the Law of the Republic of Indonesia Number 1 of 1970 concerning occupational safety and health that every worker has the right to protection for his safety in doing work for the welfare of life and increasing production and national productivity, occupational safety and health are applied to all industries according to the needs of each industry, especially the mining industry. Referring to the Minister of Energy and Mineral Resources Regulation Number 26 of 2018 concerning good mining rules and supervision of mineral and coal mining in Paragraph 1 Article 14 Number 4 mining occupational safety and health consists of at least 3 aspects, namely mining work safety which includes risk management, work safety programs which includes the prevention of accidents, fires, and other dangerous events, education and training on work safety, safety administration, emergency management, work safety inspections and accident prevention and investigation, mining occupational health aspects including worker/labor health programs, hygienic and sanitation, ergonomics, management of food, drink, and nutrition of workers/labor, and/or diagnosis and examination of occupational diseases and aspects of the mining work environment which contain company regulations, measurement, assessment and control of working environmental conditions. Implementation of the Mining Safety Management System (SMKP) in accordance with the Decree of the Minister of Energy and Mineral Resources Number 1827 K 30 MEM 2018 concerning guidelines for the implementation of good mining engineering principles where the application of the Mining Safety Management System (SMKP) is assessed at least once a year, whether audit is carried out by internal parties or externally appointed in accordance with the terms and conditions of applicable law. This research is intended to develop a mining safety management system at PT. Gunung Kulalet in accordance with the current applicable law, the SMKP assessment approach based on the internal audit matrix of the SMKP implementation has a score of 81.6% which is included in the minor category requiring evaluation, adjustment to legal regulations and controls that need to be improved. Abstrak. Penerapan Sistem Manajemen Keselamatan Pertambangan (SMKP) dalam penelitian ini memiliki landasan hukum menjalankan perintah Undang-Undang Republik Indonesia Nomor 1 Tahun 1970 tentang keselamatan dan kesehatan kerja bahwasanya setiap tenaga kerja berhak mendapat perlindungan atas keselamatannya dalam melakukan pekerjaan untuk kesejahteraan hidup dan meningkatkan produksi serta produktivitas Nasional, keselamatan dan kesehatan kerja diterapkan pada semua industri sesuai dengan kebutuhan industri masing-masing terutama pada industri pertambangan. Mengacu kepada Peraturan Menteri ESDM Nomor 26 Tahun 2018 tentang kaidah pertambangan yang baik dan pengawasan pertambangan mineral dan batubara pada Paragraf 1 Pasal 14 Nomor 4 keselamatan dan kesehatan kerja pertambangan paling sedikit terdiri atas 3 aspek yaitu keselamatan kerja pertambangan yang meliputi manajemen risiko, program keselamatan kerja yang meliputi pencegahan terjadinya kecelakaan, kebakaran, dan kejadian lain yang berbahaya, pendidikan dan pelatihan keselamatan kerja, administrasi keselamatan kerja, manajemen keadaan darurat, inspeksi keselamatan kerja dan pencegahan dan penyelidikan kecelakaan, aspek kesehatan kerja pertambangan meliputi program kesehatan pekerja/buruh, higienis dan sanitasi, ergonomis, pengelolaan makanan, minuman, dan gizi pekerja/buruh, dan/atau diagnosis dan pemeriksaan penyakit akibat kerja dan aspek lingkungan kerja pertambangan yang memuat peraturan perusahaan, pengukuran, penilaian dan pengendalian terhadap kondisi lingkungan kerja. Penerapan Sistem Manajemen Keselamatan Pertambangan (SMKP) sesuai dengan Keputusan Menteri ESDM Nomor 1827 K 30 MEM 2018 tentang pedoman pelaksanaan kaidah teknik pertambangan yang baik di mana penerapan Sistem Manajemen Keselamatan Pertambangan (SMKP) dilakukan penilaian minimal audit satu kali dalam satu tahun baik dilakukan oleh pihak internal maupun eksternal yang ditunjuk sesuai syarat dan ketentuan dari hukum yang berlaku. Penelitian ini dimaksud untuk menyusun sistem manajemen keselamatan pertambangan di PT. Gunung Kulalet sesuai dengan hukum yang berlaku saat ini, pendekatan penilaian SMKP berdasarkan matrik audit internal penerapan SMKP memiliki nilai 81,6 % termasuk kedalam kategori minor diperlukan evaluasi, penyesuaian dengan regulasi hukum serta pengendalian yang perlu ditingkatkan.